TO THE PROBLEM OF IMPROVING THE QUALITY OF PREPARATION MODERN PRIMARY SCHOOL TEACHER - N.I. Bilokonna (Academy of Cognitive and Natural Sciences, 2007)
The problem of increasing the quality of a modern primary school teacher training.